Causes and consequences of obesity: epigenetics or hypokinesis? - Graham MR; Baker JS; Davies B (Diabetes, Metabolic Syndrome and Obesity, 2015)
Michael R Graham,1 Julien S Baker,2 Bruce Davies3 1Llantarnam Research Academy, Cwmbran, Torfaen, UK; 2Exercise Science Research Laboratory, Institute of Clinical Exercise and Health Science, School of Science, University of the West of Scotland, Hamilton, UK; 3Science Department, University of South Wales, Newport, UKEpigenetics can be defined as the study of heritable changes that affect gene function without modification of the deoxyribonucleic acid (DNA) sequence.1 The transfer of epigenetic marks through generations is not well understood, and their transmission is in dispute.2 Epigenetic marks are tissue-specific and include DNA methylation and histone modifications that mediate biological processes, such as imprinting (Figure 1). Many imprinted genes are regulators of gene expression controlling growth. Imprinting disorders often feature obesity as one of their characteristics.3